A method integrating deterministic and stochastic approaches for the simulation of voltage unbalance in electric power distribution systems. - Yaw-Juen Wang (IEEE Transactions on power systems)
This paper deals with modeling, analysis and Monte Carlo simulation of three-phase voltage unbalance based on data measured from a 69/11-kV distribution substation. Random variation of the voltage unbalance factor is modeled with the aid of correlated Gaussian random variables that represent random variations in three-phase active and reactive powers. Also presented in this paper is a network reduction technique using multiple-port Thevenin equivalent circuits that allows the Monte Carlo simulation to be carried out faster. Comparison of simulated and recorded probability distributions of voltage unbalance factors is given, and good agreement has been obtained